EFFECT OF CINNAMON (CINNAMOMUM CASSIA) INTERVENTION ON METABOLIC FEATURES OF ADULT MALE WITH TYPE 2 DIABETES - RICHA SONI; VIBHA BHATNAGAR (International Journal of Pharma and Bio Sciences, 2015)
The present study was conducted to determine the effect of oral administration of cinnamon (Cinnamomum cassia) on type 2 diabetic males. Thirty subjects were randomly divided into two groups (15 in each) experimental and control. Experimental group was supplemented with 2 g cinnamon powder filled in capsules (four capsules/day/person) for six weeks. Another group served as control. Body mass index (BMI), blood pressure and lipid profile were estimated at the initial level (0 day), after three weeks and finally after six weeks. After intervention the mean systolic blood pressure (SBP), serum cholesterol (SC) and Low density lipoprotein (LDL) levels were reduced significantly (P<0.001) in experimental group (SBP: 126.13 to 121.40 mmHg, SC: 183.66 to 164.93 mg/dl, LDL: 104.73 to 89.93 mg/dl) compared with control group (SBP: 134.06 to 133.2 mmHg, SC: 173.93 to 179.33 mg/dl, LDL: 98.06 to 92.26 mg/dl). A reduction in BMI, diastolic blood pressure (DBP), serum triglycerides (TG), and very low density lipoprotein (VLDL) was observed at six weeks compared to baseline in the experimental group however the changes were not statistically significant. There was slight improvement in high density lipoprotein (HDL) of experimental group but not significant. Whereas, no significant change in any parameter of control group was observed.